قاعدة"الإعانة على المحظور محظورة": دراسة تأصيلية تطبيقية على المشاركة الإجرامية بالتسبب في قانون العقوبات الإماراتي - براف، دليلة محمد (جامعة الشارقة, 2023)
يقدم هذا البحث دراسة تأصيلية تطبيقية لقاعدة: "الإعانة على المحظور محظورة"، حيث جلى مضمونها، وأوضح أدلتها، وأبرز عناصرها وشروط إعمالها، وأنزلها على ما استجد في الفقه الجنائي المعاصر، وذلك بتخريج المعاقبة على المشاركة الإجرامية بالتسبب المقررة في قانون العقوبات الإماراتي عليها، ولو كان بفعل مباح. وقد استوى ذلك في أربعة مباحث الأول في مضمون القاعدة، الثاني: في تأصيل القاعدة وبيان عناصرها، الثالث: في شروط إعمالها، أما الرابع ففي تطبيق القاعدة على المشاركة الإجرامية بالتسبب في قانون العقوبات الإماراتي. ويصل البحث إلى ما يلي: 1. لا يستقيم إعمال القاعدة وتنزيلها على محلها إلا بمراعاة شروط نص عليها الفقهاء. 2. تجريم القانون الإماراتي لبعض صور المشاركة الإجرامية بالتسبب مبني على قاعدة "الإعانة على المحظور محظورة، والمشرع لم يخرج عن القواعد الفقهية ذات الصلة، والمقاصد الشرعية المبنية على الزواجر في تقريره لهذه العقوبة، كما راعي في ذلك المآلات الشرعية، الجالبة للصلاح والدافعة للضرر. This paper conducts a fundamentalist applied study of the rule: "the assistance on the prohibited is prohibited", by clarifying its substance, evidence, most prominent elements and the conditions of its implementation. It also reveals its connections with the new developments in contemporary criminal jurisprudence, by justifying the punishment for the causative criminal participation established in the UAE Penal Code, even if it was by a permitted act. The study includes four sections: the first section regards the substance of the rule; the second deals with the rooting of the rule and the clarification of its elements; the third section draws on the conditions of its implementation, while the fourth one concerns the application of the rule of the causative criminal participation in the UAE penal law. The findings of the study include the following: (1) the realization of the rule and its application shall not be valid unless the conditions stipulated by the jurists are observed; and (2) the UAE law’s criminalization of some forms of causative criminal participation is based on the rule of "the assistance on the prohibited is prohibited". Besides, the legislation did not deviate from the relevant jurisprudential rules and from sharia intents based on restriction in determining the punishment, as it took into account the legal outcomes that bring goodness and ward off harm.
Keywords: العلوم الشرعية -- الفقة الإسلامي -- أحداث الأمة